Acanthotetilla celebensis sp. nov., a new species from North Sulawesi, Indonesia (Porifera: Demospongiae: Spirophorida: Tetillidae) - de Voogd, Nicole J.; van Soest, Rob W. M. (Zootaxa, 2007)
A new megacanthoxea- bearing tetillid Acanthotetilla celebensis sp.nov. (Porifera: Demospongiae: Spirophorida: Tetillidae) is described from North Sulawesi, Indonesia. The new species is compared with all other (four) Acanthotetilla species occurring in the Indian Ocean and the West Indies. The new species differs from these other species by the overall morphology, and especially the presence of two sizes of megacanthoxeas. This is the first record of Acanthotetilla in Indonesia.